Surrogate Markers for Hepatitis B Virus Covalently Closed Circular DNA - Tu, Thomas; Bömmel, Florian van; Berg, Thomas (Seminars in Liver Disease, 2022)
Chronic infection with the hepatitis B virus (HBV) is one of the most common causes of liver disease worldwide. Chronic HBV infection is currently incurable because of the persistence of the viral template for the viral transcripts, covalently closed circular deoxyribonucleic acid (cccDNA). Detecting changes in cccDNA transcriptional activity is key to understanding fundamental virology, determining the efficacy of new therapies, and deciding the optimal clinical management of HBV patients. In this review, we summarize surrogate circulating biomarkers that have been used to infer cccDNA levels and activity in people with chronic hepatitis B. Moreover, we outline the current shortcomings of the current biomarkers and highlight the clinical importance in improving them and expanding their use.
Keywords: Covalently Closed Circular DNA; viral persistence; biomarkers; liver cancer; liver disease